Communication Needs and Social Resilience in the Era of Capital Relocation: Evidence from the Nusantara Capital Region - Sitti Syahar Inayah; Abubakar Idham Madani; A Rivai Beta; Miftahul Huda (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to analyze the relationship between demographics, communication needs, and social resilience of communities in the core area of the Indonesian Capital City (IKN), specifically in Sepaku District, Penajam Paser Utara Regency, East Kalimantan. This study used a survey method with a quantitative correlational approach. The sample consisted of 95 respondents randomly selected from a population of 2,094 households in three villages: Pemaluan, Bumi Harapan, and Bukit Raya. Data were collected through a questionnaire that had been tested for validity and reliability, with variables of communication needs (cognitive, affective, and integrative dimensions) and social resilience (persistence, strength, optimism, and empathy). Data analysis used the Pearson correlation test and the Kruskal–Wallis test to examine the relationship between demographic variables and social resilience. The findings indicated a significant correlation between education level and social resilience (H = 8.681; p = 0.034), suggesting that education enhances the community's adaptive capacity. In contrast, gender (p = 0.932) and participation in village meetings (p = 0.201) did not show significant differences in the level of social resilience. Furthermore, communication needs had a positive and significant relationship with social resilience (r = 0.249; p = 0.015). Among its dimensions, integrative needs showed a significant contribution independently (p = 0.011; rÂ² = 0.261), while the cognitive and affective dimensions were not significant when tested separately. These results validate that addressing communication needs, especially the integrative aspect associated with social interaction and community cohesion, is essential for enhancing community resilience in regions experiencing swift transformation. Therefore, a transparent, participatory, and inclusive public communication strategy is a key factor in supporting social resilience and the development aspirations of the National Capital.